PENGARUH LAMA PERENDAMAN DAN KONSENTRASI GIBERELIN (GA3 ) TERHADAP VIABILITAS BENIH KAKAO (Theobroma cacao L.) - Supardy, Supardy; Adelina, Enny; Made, Usman (AGROTEKBIS, 2016)
Cocoa is one of the national commodity and plays an important role for the economy of Indonesia, especially in terms of farmerâs income and source of foreign exchange Cocoa seeds are recalcitrant i.e. prone to drought, sensitive to temperature and humidity. Cacao seeds have no dormancy, low storage capacity and sensitive to environmental changes. This study aimed to determine soaking time periods and concentration of gibberellin (GA3) for best cocoa seed viability. The study was conducted in the Seed Laboratory of Faculty of Agriculture, Tadulako University from March to April 2016.Â It was arranged in a Completely Randomized Design with two factors. The first factor is the time length of soaking i.e. 2 h, 4 h, and 6 h while the second factor is the concentration of gibberellins i.e. 5 ppm, 10 ppm, and 15 ppm. Thus there were 9 treatment combinations and replicated 3 times resulting in 27 experimental units where each unit consisting of 20 grains of seed.Â Data was analyzed using Variance Analysis and then continued with the Honestly Significant Difference if there is a significant effect.Â The research results showed that the interaction effect between the length of time and the gibberellin concentrations is significant on root length but not significant on germination rate and root volume.Â Key Words : Soking time, and gibberellin concentration.Â